The Changing Empirical Definition of Money: Some Estimates from a Model of the Demand for Money Substitutes - Belongia, Michael T.; Chalfant, James A. (Journal of Political Economy, 1989)
Interest-bearing checkable deposits are examined to test whether they should be included in measures of the U.S. money stock. Both Divisia and traditional simple-sum aggregates are constructed on the basis of tests for weak separability in a model of the demand for financial assets. Using nonparametric demand analysis, we find that several groups of assets are compatible with aggregation theory. We find empirical support for a narrow measure consisting of the components of current MIA. In tests based on a St. Louis equation and in terms of controllability, a Divisia aggregate performs better than the simple-sum MIA measure.